PREDOMINANCE AND DETECTION OF DIFFERENT EIMERIA SPECIES CAUSING COCCIDIOSIS IN LAYER CHICKENS - H. A. Bachaya; M. A. Raza; M. N. Khan; Z. Iqbal; R. Z. Abbas; S. Murtaza; N. Badar (Journal of Animal and Plant Sciences, 2012)
Poultry sector is not only the source of animal protein it also plays a vital role in the employment generation. This organized and vibrant sector is adversely affected by the protozoan parasites of the genus Eimeria which causes Coccidiosis. During the months of July 2009 to June 2010, 500 gut samples of layer chickens along with 250 faecal droppings (litter samples) were collected for the detection of different Eimeria species (coccidian parasite) predominance in the different localities of district Muzaffar garh. Four different species of Eimeria i.e. E. maxima, (30.20%), E. tenella, (39.93%), E. mitis, (19.13%) and E. necatrix (10.74 %) were isolated from 298/500 (59.60%) infected gut samples. The results also indicated that young layer chickens (60.16%) have greater infection ratio as compare with adults (37%). In addition to this it was also observed that highest predominance of coccidiosis was scrutinized during the month of September (73.33%) while lowest during April (42.86%).
Keywords: Predominance; eimeria species; coccidiosis; layer